THE STATUS OF SIRA (CUSTOM) AMONG THE EVIDENCES OF OPINIONS CONCERNING THE INFANT’S CONTRACTS دوره51 شماره3 سال1398 - ????, ?? ?? ?????; ?????, ???? ???; ?????, ??????? (???????? ??????? ?????? ????)
Sira, meaning the continued way and method, is a manifestation of custom which has in contemporary Usuli works gained an unprecedented place in the inference of religious rules and despite all efforts by Usulis to delimit its thematic aspects and the conditions of its authority, there are problems with its accurate and systematic application from the aspect of jurisprudential functions and a sort of diversity of opinions and disagreement is noticeable in this regard. This paper, through a case study method, has studied the status of the conduct of wise and the custom of the people of the religion among the evidences of opinions regarding the infant's contracts and after a quick review of semantics of Sira and infant and an overview of other evidences of opinions regarding the infants contracts, has attempted to give a report on the opinions of a number of Islamic jurists with regard to the status of Sira in declaring validity or invalidity of such contracts. The results of this research show that in applying Sira as evidence, a spectrum of opinions has emerged and their contradiction indicates considerable diversity among the jurisprudential commentators and more than ever, reveals the necessity of regulating the jurisprudential and Usuli thoughts in this regard.